2021
DOI: 10.21769/bioprotoc.3945
|View full text |Cite
|
Sign up to set email alerts
|

Strategy of Isolating ‘Primed’ Tumor Initiating Cells Based on Mitochondrial Transmembrane Potential

Abstract: Various stem cells have been found to be dependent on mitochondrial energetics. The role of mitochondria in regulating the self-renewal of normal stem cells and stem-like tumor initiating cells (TICs) is increasingly being appreciated. We proposed that TIC populations have a sub population of cells that are "primed" by mitochondria for self-renewal. Using ovarian cancer model, we have developed a protocol to identify and isolate these "primed" cells using Fluorescence-Assisted Cell Sorting (FACS). We combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Adaptation to glucose-deprived condition of the peritoneum by switching to oxidative metabolism is thought to maximize the survival of ovarian cancer stem cells and promote metastasis and tumor growth at distal sites. Consistent with this hypothesis, segregation of ovarian cancer stem cells with higher relative mitochondrial transmembrane potential yields cells with more potent tumor-initiating and spheroid-forming properties [48]. Using an immunodeficient murine xenograft model, we directly compared the survival of CAP cells injected into the peritoneum after growth over ULP as spheroids with the survival of TOV-LT cells injected into the peritoneum after growth over ULP as loose clumps.…”
Section: Discussionmentioning
confidence: 79%
“…Adaptation to glucose-deprived condition of the peritoneum by switching to oxidative metabolism is thought to maximize the survival of ovarian cancer stem cells and promote metastasis and tumor growth at distal sites. Consistent with this hypothesis, segregation of ovarian cancer stem cells with higher relative mitochondrial transmembrane potential yields cells with more potent tumor-initiating and spheroid-forming properties [48]. Using an immunodeficient murine xenograft model, we directly compared the survival of CAP cells injected into the peritoneum after growth over ULP as spheroids with the survival of TOV-LT cells injected into the peritoneum after growth over ULP as loose clumps.…”
Section: Discussionmentioning
confidence: 79%
“… 1 Quantify the abundance of neoplastic stem cells using a tumorsphere assay with Extreme Limiting Dilution Analysis statistics, as described in our previously published step by step protocol. 2 Enrichment of neoplastic stem cells in the TF1 population can be confirmed by comparing the quantified abundance of stem cells (frequency) obtained in step 15 between clones transformed with 1 nM TCDD (TF1) or 10 nM TCDD (TF10) and the Parental population. To confirm the unique mitochondrial structure related to mitochondrial priming in the TF1 population, perform the single cell mitochondrial structural analyses (described in our previously published step by step mito-SinCe 2 protocol 4 ) on Mitotracker green stained cells (described in our previously published step by step protocol 5 ).…”
Section: Step-by-step Methods Detailsmentioning
confidence: 98%
“… 2 Enrichment of neoplastic stem cells in the TF1 population can be confirmed by comparing the quantified abundance of stem cells (frequency) obtained in step 15 between clones transformed with 1 nM TCDD (TF1) or 10 nM TCDD (TF10) and the Parental population. To confirm the unique mitochondrial structure related to mitochondrial priming in the TF1 population, perform the single cell mitochondrial structural analyses (described in our previously published step by step mito-SinCe 2 protocol 4 ) on Mitotracker green stained cells (described in our previously published step by step protocol 5 ). Note: From this step onwards TF1 population will be considered as the mpSC enriched population, while the TF10 and P populations will be considered as neoplastic and parental non-neoplastic controls, respectively.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, an elevated mitochondrial fusion state, sustained by mitofusin, can drive immortalization of neoplastic stem cells to support tumorigenesis in a Drosophila model (Bonnay, Veloso et al, 2020). Using analyses of single cells, we reported that neoplastic ovarian cells with minimum mitochondrial fission are found within a (Aldh marked) neoplastic stem cell sub-population that has >10 folds self-renewal and proliferation ability compared to the other (Aldh marked) neoplastic stem cell sub-population (Spurlock, Gupta et al, 2019, Spurlock, Hanumanthu et al, 2021. Thus, we proposed, that a repressed mitochondrial fission state may prime neoplastic stem cells towards maximizing their potential of self-renewal and proliferation.…”
Section: Introductionmentioning
confidence: 95%